2020
DOI: 10.3390/ma13245735
|View full text |Cite
|
Sign up to set email alerts
|

Research into the Effect of Grain and the Content of Alundum on Tribological Properties and Selected Mechanical Properties of Polymer Composites

Abstract: The subject of the research is a polymer composite with a matrix base of epoxy resin L285 cured with H285 hardener, and a physical modifier of friction in the form of alundum. The article presents an analysis of findings of tribological examinations. The authors evaluated the influence of the modifier properties in the form of alundum, i.e., mass share and grain size, on the abrasive wear of a composite, defined as loss of weight as well as on roughness parameters and selected mechanical properties. The tribol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Polymers are lightweight have good specifi c strength. Abrasive wear is one of the dominant deterioration processes in polymer tribology [7]. Machine parts such as chute bushings, roller guides, automotive reciprocating parts, agricultural equipment, cams and clutch components, etc., can undergo severe wear [1].…”
Section: Introductionmentioning
confidence: 99%
“…Polymers are lightweight have good specifi c strength. Abrasive wear is one of the dominant deterioration processes in polymer tribology [7]. Machine parts such as chute bushings, roller guides, automotive reciprocating parts, agricultural equipment, cams and clutch components, etc., can undergo severe wear [1].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, research has been conducted to determine the influence of various inorganic substances on the tribological properties of polymer composites. These include TiO 2 , TiC, Al 2 O 3 , ZnO, SiC, CuO, ZrO 2 , SiO 2 , Si 3 N 4 , CaCO, and ZrO 2 [ 26 , 27 , 28 , 29 ]. The various amounts of micro- and nano-scale particles (TiO 2 and CaSiO 3 ) were introduced into an epoxy polymer matrix for its reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [7], the authors showed the lack of linear dependencies between the properties examined, such as mass share and grain size, roughness parameters, and selected mechanical properties and the composition of the polymer composite with a matrix base of epoxy resin L285 cured with H285 hardener, and a physical modifier of friction in the form of alundum. The authors concluded that alundum of grain sizes equal to F220 and F240 exerted the best influence on the reduction of abrasive wear of the tested samples.…”
Section: Introductionmentioning
confidence: 99%